2018
DOI: 10.3390/ijms20010100
|View full text |Cite
|
Sign up to set email alerts
|

APIM-Mediated REV3L–PCNA Interaction Important for Error Free TLS Over UV-Induced DNA Lesions in Human Cells

Abstract: Proliferating cell nuclear antigen (PCNA) is essential for the organization of DNA replication and the bypass of DNA lesions via translesion synthesis (TLS). TLS is mediated by specialized DNA polymerases, which all interact, directly or indirectly, with PCNA. How interactions between the TLS polymerases and PCNA affects TLS specificity and/or coordination is not fully understood. Here we show that the catalytic subunit of the essential mammalian TLS polymerase POLζ, REV3L, contains a functional AlkB homolog 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The ATX-101/AEE788 combination significantly reduced the percentage of viable 67NR cells compared to single treatments in vitro ( Figure 1A). We have previously shown that the biological effects of ATX-101 depends on its PCNA affinity, and that a peptide with reduced PCNA binding affinity (ATX-A) has no biological effect [17,18,21,22]. Also in this study, ATX-A had much lower effect on viability than ATX-101, and importantly did not enhance the growth inhibiting effect of AEE788 ( Figure 1A).…”
Section: Atx-101 Increases the Anti-cancer Efficacy Of An Egfr/her2/vsupporting
confidence: 47%
See 2 more Smart Citations
“…The ATX-101/AEE788 combination significantly reduced the percentage of viable 67NR cells compared to single treatments in vitro ( Figure 1A). We have previously shown that the biological effects of ATX-101 depends on its PCNA affinity, and that a peptide with reduced PCNA binding affinity (ATX-A) has no biological effect [17,18,21,22]. Also in this study, ATX-A had much lower effect on viability than ATX-101, and importantly did not enhance the growth inhibiting effect of AEE788 ( Figure 1A).…”
Section: Atx-101 Increases the Anti-cancer Efficacy Of An Egfr/her2/vsupporting
confidence: 47%
“…php), and several APIM-containing proteins are involved in the MAPK and PI3K/Akt pathways acting downstream of VEGFR and EGFR [20]. A cell-penetrating APIMcontaining peptide (ATX-101) can disrupt PCNA from interacting with APIM-containing proteins [17,21,22]. ATX-101 may therefore simultaneously impair several signaling pathways considered therapeutic targets in multiple cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the importance of APIM in HLTF for colocalization with PCNA in replication foci, HLTF and HLTF F960A were overexpressed together with APIM-peptides and PCNA. The intensity of YFP-HLTF in PCNA foci was significantly reduced by co-expression of KFIVK-CFP (APIM in HLTF), and an even stronger reduction could be achieved by overexpression of RWLVK-CFP, an APIM-version with increased PCNA-affinity [36] ( Figure 1E,F, quantified in G). The intensity of YFP-HLTF F960A in PCNA foci was initially stronger than YFP-HLTF; however, after overexpression of APIM-peptides (KFIVK-CFP or RWLVK-CFP), foci intensity was reduced to the same or lower level as measured for YFP-HLTF ( Figure 1I,J, quantified in K).…”
Section: Apim In Hltf Is a Functional Pcna Interacting Motifmentioning
confidence: 98%
“…Data suggest that cellular stress, e.g., such as replication stress, is important for increased APIM-PCNA affinity [17,24,26,27,[32][33][34]. Indeed, functional APIM is verified in three proteins directly involved in DDT, ZRANB3 [17], TFII-I [24,35], and the catalytic subunit of POLζ, REV3L [36], and in two proteins involved in the regulation of TS, FBH1 [28], and RAD51B [24]. Here we show that APIM in both HLTF and SHPRH interact with PCNA, and that the binding of HLTF and SHPRH to PCNA is important for their function in DDT after UV-induced DNA damage.…”
Section: Introductionmentioning
confidence: 99%